Neutrally Stable Outcomes in Cheap Talk Games - Abhijit Banerjee; Jörgen W. Weibull (The Research Institute of Industrial Economics (IUI), 1996)
This paper examines equilibrium and stability in symmetric two-player cheap-talk games. In particular, we characterize the set of neutrally stable outcomes in finite cheap-talk 2 x 2 coordination games. This set is finite and functionally independent of risk-dominance relations. As the number of messages goes to infinity, this set expands to a countable limit set that has exactly one cluster point, the Pareto efficient Nash equilibrium payoff. In contrast, the set of outcomes that are strategically stable for some finite message set is shown to be dense in the interval spanned by the Nash equilibrium payoffs of the game. We also show that the limit set of neutrally stable outcomes coincides with the set of neutrally stable outcomes for countable infinite message sets.
Keywords: C70; C70; C73; 330; GAME; THEORY; Spieltheorie; Nash-Gleichgewicht; Theorie